Analyzing Legal Ramifications for Auction Winners: A Case Study of Bekasi and Makassar Court Decisions on Auction Cancellations - Dwi Handayani; Muhammad Ilyas; Teguh Kuncoro (Universitas Negeri Semarang, 2023)
This article starts with the auction of the valid execution and in accordance with the minutes of auction of the Bekasi State Wealth and Auction Service Office (KPKNL) Number 225/2013 with the winner of the auction in good faith, but the auction was canceled by the court in the decision of the Bekasi State Court Number 412/Pdt.G/2015/PN.Bks on the claim of the legal owner of the collateral object against Auction applicant. The creditor filed for the execution of the dependent rights under Article 6 of the Law on Dependent Rights Number 4/1996 on the basis of default. Furthermore, the decision was appealed and then continued with cassation and finally the Review of case Number 664PK/PDT/2020 with the decision to reject the application for cassation and Judicial Review. Weaknesses in the auction rules result in the rights of auction winners not being accommodated and not protected by law. This article is interesting to researched and is the first time it has happened and has not been regulated in the Technical Guidelines of the Minister of Finance Regulation Number 213/PMK.06/2020. As a comparison, the case in Makassar State Court Number 73/Pdt.G/2023. With the method of statutory approach, cases, and theories of laws, then analyzed in the way of legal reasoning, and interpretation of laws. The results showed the legal consequences of the rights of the auction winners due to court decisions, namely experiencing material losses that must be borne by the Bekasi District Court decision. Solutions offered, updating the Vendu Reglement Ordonantie on the conduct of auctions in Indonesia; perfecting PMK Number 2013/PMK.06/2020 concerning technical guidelines legal. The purpose of the study, to examine the legal consequences of the rights of auction winners because the court decision that decided the auction has no legal force.